1988
DOI: 10.1093/infdis/157.5.1032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Translocation Rates of Various Indigenous Bacteria from the Gastrointestinal Tract to the Mesenteric Lymph Node

Abstract: Bacterial translocation is defined as the passage of indigenous bacteria from the gastrointestinal (GI) tract through the lamina propria to the mesenteric lymph nodes (MLN) and other organs. We compared the relative abilities of various aerobic, facultatively anaerobic, and obligately anaerobic bacteria to translocate from the GI tract to the MLN in gnotobiotic mice colonized with single strains of bacteria. Indigenous gram-negative enteric bacilli translocated in large numbers to the MLN, whereas gram-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
1
10

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(122 citation statements)
references
References 30 publications
6
105
1
10
Order By: Relevance
“…The rate of translocation to the liver, spleen, and mesenteric lymph nodes was 100% in both groups at both time points. Although it has been reported that anaerobic bacteria have a lower tendency to translocate, 24 we found, in this experiment, that anaerobic bacteria translocated at the same rate as aerobic bacteria. Under normal conditions a series of protective mechanisms contribute to prevent bacterial translocation except in one rat out of six (16%).…”
Section: Histological Studycontrasting
confidence: 76%
See 2 more Smart Citations
“…The rate of translocation to the liver, spleen, and mesenteric lymph nodes was 100% in both groups at both time points. Although it has been reported that anaerobic bacteria have a lower tendency to translocate, 24 we found, in this experiment, that anaerobic bacteria translocated at the same rate as aerobic bacteria. Under normal conditions a series of protective mechanisms contribute to prevent bacterial translocation except in one rat out of six (16%).…”
Section: Histological Studycontrasting
confidence: 76%
“…Blood samples were expressed per milliliter of blood. ''Total anaerobic plate group were subjected to portal pressure measurement at 24 and 48 hours (6 at each time). A venous catheter (outside count'' was performed by placing the samples on BHI and incubating under anaerobic condition (Gas Pack system, Gas diameter 0.25 mm) was passed through a peripheral branch of the superior mesenteric vein and was advanced to the porPack; Becton Dickinson Microbiology Systems, MD) at 37ЊC for 3 days.…”
Section: Measurement Of Portal Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Organisms of group Enterobacteriaceae continues to be a major cause of Gram negative aerobic bacillary bacteraemia. This increase in invasion by Gram negative bacilli is perhaps because the organisms translocate more efficiently from the gastro-intestinal tract than do other bacteria 5,6 . ICU associated infections are mostly due to Staphylococcus aureus & Coagulase negative Staphylococcus epidermidis arising from contaminated intra-vascular devices like artificial heart valves, intravenous and intraarterial catheters 7 .…”
Section: Introductionmentioning
confidence: 99%
“…First, translocation of bacteria to mesenteric lymph nodes and the portal circulation may result in systemic bacteremia with subsequent peritoneal seeding, resulting in peritonitis. It has been shown that gram-negative aerobic enteric bacteria translocate more efficiently from the gastro-intestinal tract than other bacteria, especially obligate anaerobes [11,12]. It could be possible that colonoscopy predisposes to bacterial translocation and subsequent hematogenic peritonitis.…”
mentioning
confidence: 99%